SIMPLIFIED TAXATION, ACCOUNTING AND REPORTING SYSTEMS: THE EXPERIENCE OF UKRAINE, POLAND AND FRANCE (Economic journal of Lesya Ukrainka Volyn National University, 2025)
Introduction. In the modern context of globalization and the integration of national economies, taxation systems — particularly those affecting small businesses and self-employment — play an increasingly important role. Simplified taxation regimes reduce administrative and fiscal burdens, stimulating entrepreneurial activity. Ukraine, France, and Poland have developed their own models of such systems, reflecting diverse approaches to small business regulation in line with European standards.The purpose of the article. The purpose of this article is to conduct a comparative analysis of simplified taxation systems for individual entrepreneurs in three jurisdictions — Ukraine, France, and Poland — with a focus on key differences in tax rates, income limits, hiring rights, social contributions, and legal restrictions.Methods. The research applies methods of comparative analysis, systemic generalization, and graphical visualization to clearly illustrate the parameters of simplified taxation systems. The analysis is based on current legal frameworks in Ukraine, France, and Poland, as well as official analytical sources and academic publications.Results. The article presents a comparative review of three simplified taxation models applied to individual entrepreneurs in Ukraine, France, and Poland. It examines key aspects such as eligibility criteria, income thresholds, tax rates, permitted types of activity, rules for hiring employees, and social contributions. Ukraine’s system is structured into four groups of single tax payers with clearly defined parameters. France’s Entreprise Individuelle includes three regimes that vary according to turnover and allow a gradual transition between tax forms. Poland’s JDG offers four taxation methods, including the highest income limit (up to €2 million) under simplified reporting. A comparative diagram visually illustrates the range of possibilities for entrepreneurs under each system.Conclusions. Each of the examined systems has its own strengths and limitations. The Ukrainian model is detailed and suitable for small businesses but has relatively low income thresholds. The French system prioritizes social protection and offers a flexible transition between regimes. The Polish approach is the most liberal in terms of activity volume but requires significant social contributions. The findings are relevant for entrepreneurs and for shaping tax policy in the context of European integration.
Keywords: taxation, accounting, reporting, FOP, Entreprise Individuelle, Jednoosobowa Działalność Gospodarcza, tax system, tax rates, income limits, social contributions, small business, EU.